Micro plastic injection molding - Koh, Rachel Sheng Lin (2015)
The plastic injection molding process allows complex geometries to be made in short time and has thus played a critical role in the mass production of parts. The injection molding technique has been further developed for the fabrication of micro parts for field applications such as micro-mechanics (micro gears, micro pumps, etc.), micro optics (fiber connectors, waveguides, etc.) as well as information storage (CDs, DVDs, etc.). The adapted process is called micro injection molding. In this project, Polymethyl Methacrylate (PMMA) was used to mold circular discs with micro channel inserts to investigate the effect that process parameter settings have on the micro injection molding process. In the initial phase of the project, the one-factor-at-a-time experimental method was used and the molded micro channel parts were analyzed using the confocal imaging profiler. Following that, the Taguchi method was used for a more systematic experimental analysis. After confocal measurement, the results were interpreted using the quality improvement software, Minitab 17. For both experimental methods, the process parameters used was barrel temperature, mold temperature, injection pressure and holding pressure. In conclusion, the parameter setting that yielded a more favorable result for the one factor-at-a-time experiment is barrel temperature of 255°C, mold temperature of 80°C, injection pressure of 1200 bar and holding pressure of 300 bar. Similarly, for the Taguchi Method, high-level settings also yielded a more favourable result. The settings are barrel temperature of 255°C, mold temperature of 80°C, injection pressure of 1200 bar and holding pressure of 200 bar.